RANCANG BANGUN SISTEM INFORMASI PELAYANAN RESTORAN HOTEL BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER - Sihombing, Rikardo; Arnomo, Sasa Ani (Computer Science and Industrial Engineering, 2023)
The Batam view hotel restaurant is one of the service units in the hotel. Guests at the hotel generally enjoy eating and drinking at the restaurant. The manual system in the hotel restaurant often causes problems, such as guest orders that do not match those recorded by restaurant staff, guests often cancel orders because no one is taking orders, and Guests often have difficulty seeing the list of food and drinks available in the restaurant. Until now, this hotel restaurant does not have an online ordering system. thus resulting in several work systems being constrained. This is what prompted the author to build and design a Web- based information system for this restaurant.This website will be designed with the PHP programming language and coupled with the codeigniter framework. The research method used is Research and development (R&D),This research is expected to be able to develop the restaurant into a restaurant that has an online system, so that it can increase guest satisfaction both in terms of service and providing information.